Karakteristik Fermentabilitas dalam Rumen In vitro pada Pelepah Sawit Fermentasi yang Disuplementasi Tepung Kulit Jengkol - Nurhaita Nurhaita; N. Definiati; N. Hidayah (State Islamic University of Sultan Syarif Kasim Riau, 2020)
Palm fronds are one of by-product plantation that ware potential used as animal feed. But the weaknesses were low digestibility and low nutrition. The processing of palm fronds with fermentation technology which combined with the addition of jengkol peel was one of method to improving the nutrition quality. The purpose of this study was to measure the digestibility and characteristics of rumen fluid in fermented palm oil fronds supplemented with jengkol peel powder. This study was designed in completely randomized with four treatments supplementation of jengkol peel powder at 0, 2, 4, and 6% and four groups as replications. Parameters analyzed were pH value, NH3 concentration, total VFA production, dry matter and organic matter digestibility. The data were analyzed using ANOVA and different among treatments means examined by Duncan Multiple Range Test. The result showed that the addition of jengkol peel powder at 2-6% to fermented palm fronds decreased (P<0.05) in-vitro dry matter and organic matter digestibility, rumen pH value, VFA Production and NH3 concentration. From this study it can be concluded that supplementation of jengkol peel powder on fermented oil palm fronds can reduce the digestibility of dry matter and organic matter in vitro, affecting the characteristics of rumen fluid (pH, VFA and NH3), but is still at optimal conditions for normal fermentation in rumen.